The transformaiton of Japan's environmental policy - Takao, Yasuo (Routledge, Taylor & Francis Group, 2012)
In the 1970s and 1980s, Japan was known as the leading innovator in environmental policy. Other OECD countries found much to emulate. Two decades later, Japan appears to have lost its innovative edge to other OECD countries. Why has Japan fallen from its position as the global leader? How should Japan regain its reputation? Possible causes of the rise and fall of Japanese environmental policy are examined by exploring its domestic policy subsystem, the international arena and the arena where domestic and foreign issues converge, the emerging space in which sub-national authorities have become increasingly recognised as direct contributors to global environmental strategies. Each of three approaches – the domestic/foreign divide, interaction and convergence – offers a partial answer to these questions.